Advanced footwear technology, but not acute ingestion of a ketone monoester, improves running economy in middle- and long-distance runners - Brady, A. J.; Moynagh, M. B.; Devenney, S.; Egan, B. (Medicine & Science in Sports & Exercise, 2025)
Purpose This study examined the separate and combined effects of advanced footwear technology and acute ingestion of a ketone monoester on running economy (RE), time to exhaustion, and other metabolic and cardiorespiratory parameters.